Electrostatic Solitary Waves in Electronegative Martian Plasma - Steffy Sara Varghese; Kuldeep Singh; Frank Verheest; Ioannis Kourakis (The Astrophysical Journal)
The solar wind interacts with planetary magnetospheres, generating plasma waves in both the upstream region and the magnetospheric environment. Mars, lacking an inherent magnetic field, has an induced magnetosphere formed through solar wind interaction with its ionosphere. These waves are crucial for momentum and energy exchange within the planetary plasma environment. This study focuses on the existence and dynamics of electrostatic solitary waves (ESWs) in Martian ionospheric plasma, characterized by various flowing ions. We employ a multifluid plasma model incorporating positive (streaming) ions, negative ions, and two distinct kappa-distributed electron populations to study ESW propagation in the Martian ionosphere from first principles. Linear analysis reveals four distinct modes, including a subsonic mode due to the negative-ion beam. Electrostatic waves may become unstable due to a beam instability excited at long wavelengths. Seeking stationary profile solutions, an energy balance equation is obtained in the moving reference frame, and the shape of the solitary wave can thus be predicted numerically. A meticulous analysis reveals that either positive- or negative-polarity ESWs (or both) may occur (simultaneously) in the Martian environment. In addition to conventional bipolar E-field waveforms, our theoretical model predicts the existence of wiggly bipolar pulses (supersolitary waves) and offset bipolar pulses (flat-top solitary waves) in Martian plasma. Comparison of our model’s predictions with real observational plasma parameters indicates that, like Martian magnetosheath plasma, ionospheric plasma may sustain ESWs measuring several tens of millivolts per meter.